Web-Based Citizen-Police Report System - Yee, Suzan; Nayef Abdulwahab Mohammed Alduais (Applied Information Technology And Computer Science, 2023)
Many crimes and accidents were not reported to the authorities today due to the costs and time required to go to police stations, and the laborious process. Thus, this project was developed to analyze, design, develop, and test a web-based system and mobile application for citizen to lodge police report online. Citizens can file police reports using smartphone or laptop and police can handle them easily through the system. Upon finishing, the system became an alternative way for citizen to file police report and gain trustable information. Waterfall Model was used in the development of this project. The system implemented using PHP programming language in Visual Studio Code and phpMyAdmin tool. With a test strategy and User Acceptance Test (UAT), the system lets citizens file many reports and police officers and admin quickly process and update them. When the system can track citizens, fake report limits must be considered.